Design of Biocompatible Chitosan/Polyaniline/Laponite Hydrogel with Photothermal Conversion Capability - Liying Zhang; Gao He; Yang Yu; Yu Zhang; Xiang Li; Shige Wang (Biomolecules, 2022)
In recent years, multifunctional hydrogels have received a great deal of attention because they are biocompatible and can mimic the extracellular matrix. Herein, we prepared hydrogels of biocompatible cross-linked networks with photothermal properties. In this study, a chitosan/polyaniline/laponite (COL) hydrogel with photothermal conversion capability was designed. Polyaniline was firstly grafted onto chitosan and its solution was mixed with oxidized dextran, which was then cross-linked into a hydrogel via a Schiff base reaction. Furthermore, an aluminosilicate clay material, laponite (LAP), was incorporated into the hydrogel. The swelling ratio of the COL hydrogel in various solutions was greater than 580%, and it showed good degradation ability (the mass–loss ratio was over 45% after 28 days). This composite hydrogel was demonstrated to have good photothermal conversion properties and biocompatibility at both the cell (cell viability was over 97%) and animal levels. The COL hydrogel showed a photothermal conversion efficiency of 23.7% under the irradiation of a near-infrared laser. Coupled with the osteogenic differentiation-inducing potential of LAP, the COL hydrogel has the potential to kill tumors via hyperthermia or serve as scaffolds for bone tissue regeneration.